DIAGNOSTIC METHODS AND TREATMENT OF DENGUE - Umer FAROOQ BHATTI (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2023)
74 Summary Title: Diagnostic methods and treatment of dengue Author: Umer Farooq Bhatti Key words: Aedes, Fever, PCR, Re-emergence, Vaccine. Dengue is a mosquito borne viral disease caused by infection from any of the four serotypes of dengue virus (DENV-1-4). Early laboratory diagnosis of DENV is essential for effective patient management. For confirmation of dengue through laboratory tests, it is usually recommended to use several techniques and not be limited to a single diagnostic method. Among existing diagnostic methods, serological assays are the most widely used and they are considered as mainstay of diagnosis of this disease. Because they are sensitive, rapid and cheap. NS1 ELISA and IgM ELISA are useful during acute phase of dengue infection. Rapid diagnostic tests for NS1 antigen and IgM antibody detection are a good alternative to ELISA based assays. Virus isolation is a gold standard of dengue diagnosis. But it is of limited use because it is lengthy, time consuming and requires skilled lab workers. Other molecular diagnostic methods include Real time RT-PCR (TaqMan or SYBR green), NABSA assay and RT-LAM. They have high sensitivity and specificity. The prevention of dengue can be achieved by vector control. There is no specific antiviral treatment for dengue illness. Clinical management is based on supportive therapy. The first licensed dengue vaccine, CYD- TDV (Dengvaxia), is a live attenuated, recombinant tetravalent vaccine. The vaccine contains four live attenuated recombinant dengue viruses, each representing one of the four serotypes.
Keywords: Aedes; Fever; PCR; Re-emergence; Vaccine; Aedes; Fièvre; PCR; Re-emergence; Vaccin